Teologi Pendidikan Dalam Perjanjian Lama (Kitab Meleakhi) - Fanny Yapi Markus Kaseke; Nita Rahayun (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2022)
This paper is about the biblical foundation for Christian education, the foundation found in the Old Testament, namely the book of Malachi. Christian education requires a foundation that comes from the Bible, in which it displays Christian values. Many Christian Educational Institutions, educators (teachers), students do not have sufficient